A Leaky Wave Antenna Design Based on Half-mode Substrate Integrated Waveguide Technology for X Band Applications - S. Doucha; M. Abri; H. Abri Badaoui; B. Fellah (Institute of Advanced Engineering and Science, 2017)
A new type of leaky-wave antenna (LWA) using half-mode substrate integrated waveguide (HMSIW) as the base structure is proposed in this paper. The structure consists of an array of slot, antenna designed to operate in X band applications from 8 to 12 GHz. HMSIW preserves nearly all the advantages of SIW whereas its size is nearly reduced by half. The antenna radiates one main beam that can be steered from the backward to the forward direction by changing frequency.